A SEIR Metapopulation Model for Mpox Transmission Dynamics in the DRC - Peter, Kasende Mundeke; MATONDO MANANGA, Herman; Lea Irène, Milolo Kanumuambidi; Patience, Pokuaa Gambrah (Journal of Applied Informatics and Computing, 2026)
Understanding the mechanisms of infectious disease spread is a fundamental prerequisite for any control, management, or eradication strategy. This understanding relies on the rigorous integration of biological knowledge, mathematical tools, and computational resources, which enable in-depth analysis, the formulation of approximate numerical solutions, and the simulation of the temporal evolution of the pathological phenomenon. In this study, we develop an SEIR-type compartmental model to represent the transmission dynamics of Mpox, taking into account a metapopulation structure between two interconnected geographical areas, designated as patches 1 and 2. This model allows us to integrate the effects of interregional mobility on the spread of infection. The SageMath environment (version 9.3) was used to simulate viral dynamics within each patch, incorporating migration flows between the two regions. The system equilibria were determined and adjusted based on available data. The analysis focused on calculating the basic reproduction number, studying the stability of equilibria, and evaluating parameter sensitivity. The results suggest a gradual extinction of the disease in both patches, under certain conditions relating to mobility and recovery rates. Finally, this investigation highlights the relevance of SageMath software as a powerful tool for exploring and simulating spatially structured epidemiological models, with the ability to adapt to a variety of contexts and pathologies.